Assessment of Poisonous Metal Concentration in Preferred Tissues of Two Dissimilar Classes of Ruminants in Punjab, Pakistan - Ayub, Muhammad; Zuber, Muhammad; Yousaf, Muhammad; Hussain Arshad, Shahid; Hammad Raza, Syed; Iqbal Khan, Zafar; Ahmed, Kafeel; Bibi, Zahara; Saleem Akhtar, Muhammad (Asian Journal of Chemistry, 2013)
Heavy metals are mostly considered toxic for animals as well as for humans. The purpose of this study was to determine the concentrations of copper in various organs (livers, kidneys, lungs, ribs, cerebrum, blood-serum, bones and hair) of cattle and buffaloes of both sexes with different ages, in two districts of Punjab. A total of 480 samples were collected and lead concentration was estimated by using atomic absorption spectrophotometer. Analysis of variance of data for lead concentration mostly in cerebrum, blood-serum and lungs showed significant effect (p < 0.05) of the locality and age of all classes of animals. Its level was also significant (p < 0.05) in the liver, kidney, ribs, bones and hair of animals of both sexes but reverse was true for lungs of the female cows in which Pb concentration was non-significant. It was found that the concentrations depend upon the sampling organs, animal species and locality of animals. The concentrations of lead in the liver and kidney (7.48 ± 0.33, 8.86 ± 0.56) and (8.63 ± 0.86, 8.25 ± 0.99) in the male cows of district Jhang and Toba, whereas (7.72 ± 0.41, 7.04 ± 0.62) and (8.12 ± 0.68, 6.86 ± 0.48) in the female cows of district Jhang and Toba, were found to be higher. Similarly its concentrations in the liver and kidney (7.89 ± 0.51, 9.48 ± 0.55) and (8.41 ± 0.94, 6.44 ± 0.69) in the male buffaloes of district Jhang and Toba, respectively (6.32 ± 0.49, 9.08 ± 0.45) and (8.49 ± 0.95, 5.31 ± 0.65) mg kg-1 in the female buffaloes of district Jhang and Toba and were found to be higher as compared to the critical values. In forage of district Toba, the mean ± standard error (SE) of lead concentration (22.86 ± 0.31 mg kg-1) was higher, while at Jhang, its concentration (22.18 ± 0.45) was lower as compared to the corresponding concentration (22.72 ± 0.27 mg kg-1) of control farms, respectively. In soil of district Jhang and Toba, Pb concentration (2.84 ± 0.11 and 3.62 ± 0.20 mg kg-1) was found to be higher as compared to that of control farm (1.82 ± 0.20 mg kg-1). So one should be careful in consuming liver and kidney of cows and buffaloes as the accumulation of lead in these organs is found to be very high beyond the safe limit. It is essential to use supplementation of mineral mixture to soil, forages and animals in appropriate proportion (tailored mixture) to decrease mineral toxicity and also the reproductive potential, fertility and growth rate of grazing animals can be increased.